Screening of Antitumor Bioactivity of Fungi Associated with Macro Algae and Sponge from Indrayanti Beach, Jogjakarta - Fajarningsih, Nurrahmi Dewi; Nursid, Muhammad; Chasanah, Ekowati (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2013)
This research was aimed to isolate marine derived-fungi which associated with macro algae and sponge from Indrayanti Beach, Jogjakarta and to screen the antitumor (T47D and HeLa) bioactivity of the fungi extracts. Three solid media of MEA (malt extract agar), GPY (glucose peptone yeast) and MFM (minimal fungi medium) were used as isolation medium. Each of the pure fungi isolates was then cultivated in 100 ml of liquid medium for 4 weeks at room temperature (27-28°C) in static conditions. The antitumor activity of the fungi extracts were tested against breast tumor cells (T47D) and cervical cancer cells (HeLa) using Thiazolyl Blue Tetrazolium Blue (MTT) assay method. A number of 21 isolates of fungi were isolated from 4 macro algae and 1 sponge samples. The identification of fungi isolate was conducted using combination of molecular approach (ITS1-5.8S-ITS4 DNA regions) and macro-micro morphological characteristics. Among those 21 marine fungi species isolated, MFGK-21 extract showed the best anti-servical tumor (HeLa) with an IC50 value of 240.1 µg/ml and MFGK-27 extract showed the best anti-breast tumor (T47D) with an IC50 value of 59.6 µg/ml. The MFGK-21 fungi isolate was identified as Penicillium steckii, while the MFGK-27 fungi isolate was identified as Aspergillus sydowii.